Estudio situacional de la producción y comercialización del grano de cacao en la zona de Urdaneta, Los Ríos - Araujo Contreras, Mayra Alexandra (2021)
The cultivation of cocoa (Theobroma cacao L) in Ecuador is known as the "golden seed", being one of the main products that offers greater foreign exchange, income, exports and jobs to peasant families, this crop has occupied one of the most important items in the commercial, social and environmental activity of Ecuador, followed by a world production that increases day by day, influenced by the increase in the level of demand, since this product is part of the human diet of many people , as well as for the derivation process as raw material that is given to the product. This practical work aims to carry out a situational study of the production and commercialization of the cocoa bean in the area of Ricaurte, Los Ríos, having as specific objectives: 1) Identify the socio-economic situation of the commercialization of the cocoa bean in Ricaurte. 2) Analyze the structure and operation of the cocoa production chain in the area of Ricaurte, for this analysis the use of closed-type surveys to the collection centers of said locality was used as a methodology, these surveys were carried out telematically due to the The health crisis that the country is going through, whose data were processed and interpreted with calculation of numbers (percentages) and bar graphs, the conclusions determine that the farmers do not have technical training for the advice and commercialization of the crop, lack of financing from the institutions, resulting in low prices and poor product conditions at the time of sale.